Late defoliation of ‘Chardonnay’ grapevine in subtropical highland climate - Figueiredo,Gabriel Machado de (2020)
ABSTRACT Chardonnay cultivar has shown great potential of planting and development in sites above 900m of Brazilian southeast for sparkling wines production. The quality of this product is related to vineyard climate and management, since both affect the vine development and grape composition. In this study, three defoliation orientations (east, west and east/west face), at veraison, and a group without defoliation, were compared in order to observe the impacts of this management on the productivity, grape and base wine quality. Yield, grape components, must and base wine composition were analyzed for two years. East/west defoliation increased alcohol content and decreased acidity in base wines, while the group without defoliation increased acidity, according to the higher and lower sun exposure, respectively. Defoliation at veraison increased the incidence of bunch rots. Differences in the aromatic composition of the base wines between the harvests were identified. The east/west defoliation treatment presented more intense fruity, citrus and tropical aromas. For regions characterized by subtropical highland climate (Cwb) in the Brazilian Southeast, late defoliation is not recommended since defoliated plants were more susceptible to fungus infection at flowering and berry formation.